Analisis Kemampuan Menyimak Dialog Berita Dan Petunjuk Pada Anak Sekolah Dasar (SD) - Arina Nur Salsabila; Zahrotun Siti Nur Kholimah; Shafira Azzahro; Fahrizal Akbaryanto; Sri Sukasih (Pendekar : Jurnal Pendidikan Berkarakter, 2023)
The research aims to analyze the listening skills of elementary school (SD) children in comprehending dialogue in news and instructions. It covers the ability to understand and respond to messages conveyed, including news dialogues and instructions for elementary school children. The research approach used is "Library Study,"one of the qualitative research methods, where the study is conducted in the library through the collection of books, documents, archives, and other materials. The article writing technique utilizes the IMRAD method. The research results indicate the importance of understanding the Indonesian language. In comprehending dialogue, the focus is on understanding vocabulary, context, and emotional nuances. In listening to news, children need to recognize the main information, understand facts, and the structure of the news. Comprehending instructions requires language understanding, time sequence, and instruction processing. Both extensive and intensive listening play a role in developing the listening skills of elementary school children. A holistic learning approach involving direct interaction and practical exercises helps children develop listening skills. The role of teachers, parents, and the learning environment supports the effective formation of language understanding in elementary school children.